Postpartum Uterine Involution and Embryonic Development Pattern in Chinese Holstein Dairy Cows - Lin, Yuxin; Yang, Hongzhen; Ahmad, Muhammad Jamil; Yang, Yuze; Yang, Wucai; Riaz, Hasan; Abulaiti, Adili; Zhang, Shujun; Yang, Liguo; Hua, Guohua (Frontiers in Veterinary Science, 2021)
Understanding the postpartum uterine involution pattern and embryonic development could facilitate bovine reproduction management, improve reproductive efficiency, and diagnosis of the reproductive disorder, which would contribute to the success of the dairy business. This study aimed to investigate postpartum uterine involution and embryonic developmental patterns or postconceptional marks of embryonic fetal development in Chinese Holstein dairy cows using B-mode ultrasonography. The results revealed a significant decline in the involution period with an increase of parity and age. The uterine involution period was shorter in multiparous cows when compared with cows with lower parities. Consistently, cows over 4 years old recovered faster than younger cows (2 or 3 years). Besides, the elder cows (over 4 years) had a relatively larger size of resumed cervix uteri and horns. Postpartum uterine involution pattern analysis revealed that the reproductive tract recovered very fast during the first 16 days postpartum for all the parity. Results of postconceptional marks of embryo development revealed a slow increase in diameter of the gravid uterine horn and crown-rump length (CRL) before day 60. In contrast, this increase was dramatic and rapid after the 60th day. We also established two models to estimate gestational age based on gravid uterine horn diameter or CRL. A formula was established to determine the gravid uterine horn size during postconceptional on day 30th–day 90th (r = 0.8714, P < 0.01). In addition, a significant positive correlation between CRL and gestational age (r = 0.98151, P < 0.01) was built. In conclusion, these results illustrated that parity and calving age had significant effects on uterine involution in Chinese Holstein cows. Crown-rump length and gravid uterine horn diameter are both efficient for evaluating the embryo growth. These current findings broaden the understanding of basic reproductive pattern in Chinese Holstein cows and could benefit bovine reproductive management primarily in postpartum and early pregnant cows to reduce the calving interval and avoid periparturient metabolic diseases.